Examining value-based factors in software development: A survey study in Malaysian public sector - Zakaria, Noor Azura; Ibrahim, Suhaimi; Mahrin, Mohd Nazri (Association for Computing Machinery (ACM), 2015)
Software development plays a major role in the production of software products. This process must be carefully designed in order to successfully deliver the end product, and at the same time fulfill the values desired. Value-Based Software Engineering (VBSE) aims to convert the value-neutral setting in developing software to become a more value-centric approach.This study presents exploratory survey results for the purpose of examining value-based factors that are most commonly used in software development. The survey conducted at the Malaysian public sector involving a software development team as the target population. Exploratory factor analysis was used as the main data analysis strategy in this study. The results reveal that there are 28 value-based factors that are most commonly used in software development which can be classified into four classifications(success-critical stakeholders, business strategy, project characteristics and product characteristics). Our objective in further research is to develop value-based factors profile as imperative input to conduct software process tailoring.